The role of conception on mental illness and social media in reducing social distance toward people with mental illness - Wan Ainil Husna Wan Salim; Azlina Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2022)
Social distance added challenges to people with mental illness in facing their diseases. It impacted the seeking help attitude of people with mental illness that make them lose their social function to society. This study aimed to examine the significant relationship between the conception of mental illness and social media with social distance towards people with mental illness among public university students. A cross-sectional survey was conducted on public university students in Selangor (n=384). Responses were rated on a five-point Likert scale. Bootstrapping tests were used to determine the relationship between the conception of mental illness and social media with social distance toward people with mental illness. The Result showed that conception of mental illness and social media have a significant relationship with social distance toward people with mental illness. This shows that negative conception of mental illness and negative views regarding mental illness person on social media impact social distance toward people with mental illness. Therefore, reducing social distance toward people with mental illness can enhance the seeking help attitude and social function of people with mental illness.